2011
DOI: 10.3844/ajavsp.2011.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Thyroid Hormone Concentrations and pH Values of Some GI-Tract Segments of Broilers Fed on Different Dietary Citric Acid and Microbial Phytase Levels

Abstract: Problem statement: An experiment was conducted to study the effect of microbial phytase supplementation and citric acid on thyroid activity, relative weight of lymphoid organs and pH values of some GI-tract segments in broiler chickens fed corn-soybean meal based diets. Approach: The data was analyzed using a Randomized Complete Block Design (RCBD) with factorial arrangement of 3×3, three levels of citric acids (0, 3 and 6%) and three levels of phytase (0, 500 and 1000 IU kg). There were three replicates (with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…In the current experiment, dietary inclusion of 5,000 FTU/kg of phytase influenced gastrointestinal pH. Supplementation of a microbial phytase at 250, 500, or 1,000 FTU/kg did not influence stomach pH in 32kg pigs (Radcliffe et al, 1998), gastrointestinal pH in 42-d-old broilers (Nourmohammadi et al, 2011), or ileal pH in 21-d-old broilers (Akyurek et al, 2011). However, feeding 1,000 FTU/kg of phytase significantly increased fecal pH in 53-kg pigs (Metzler et al, 2008).…”
Section: Discussionmentioning
confidence: 82%
“…In the current experiment, dietary inclusion of 5,000 FTU/kg of phytase influenced gastrointestinal pH. Supplementation of a microbial phytase at 250, 500, or 1,000 FTU/kg did not influence stomach pH in 32kg pigs (Radcliffe et al, 1998), gastrointestinal pH in 42-d-old broilers (Nourmohammadi et al, 2011), or ileal pH in 21-d-old broilers (Akyurek et al, 2011). However, feeding 1,000 FTU/kg of phytase significantly increased fecal pH in 53-kg pigs (Metzler et al, 2008).…”
Section: Discussionmentioning
confidence: 82%
“…(2008), Panda et al . (2009a), and Nourmohammadi et al . (2011) reported a significant pH reduction in the duodenum, whereas other studies found no significant pH reductions in the duodenum.…”
Section: Effects On the Ph Of The Gastrointestinal Tract (Git)mentioning
confidence: 94%
“…Studies showed the addition of CA in poultry diet contributed to decreasing the counts of pathogenic intestinal bacteria ( Tollba, 2010 ; Elnaggar and Abo El-Maaty, 2017 ; Fikry et al., 2021 ). Besides the antimicrobial activity, CA also reduce the pH of gastro-intestinal tract content ( Nourmohammadi et al., 2011 ; Fikry et al., 2021 ), improve the morphometry of small intestine ( Nourmohammadi and Afzali, 2013 ), and enhance the feed nutrients digestibility ( Nourmohammadi et al., 2012 ; Fikry et al., 2021 ). Furthermore, supplementing CA in low nutrient diets may compensate for the performance losses of broilers ( Das et al., 2012 ; Islam et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%